The Future Foreign Correspondent - Bebawi, Saba. author. aut Link
XI, 120 p. 3 illus., 2 illus. in color.
Keywords: This book articulates the skills and perspectives that future foreign correspondents need to adopt in an increasingly globalized world. By revisiting entrenched traditions in the training and practice of international reporting, The Future Foreign Correspondent examines the changing role of a correspondent, outlining aspects that will evolve, the skills that will continue to be pivotal and those becoming even more important, such as the need for greater cultural understanding within the global media sphere. This book is a must read for journalists, media students and researchers interested in understanding what needs to be taken into consideration when reporting transcultural news spheres. .